The proximate, fatty acid and mineral composition of the muscles of cultured yellowtail (Seriola lalandi) at different anatomical locations - Burke, Andrew Brian (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Animal Sciences))--University of Stellenbosch, 2011.